Effects of a structured health education on prevention of HIV risky behaviours among adolescents in Nigeria – a pragmatic randomized controlled trial. Issue 1 (31st December 2022) - Maduakolam, Ijeoma O.; Ogbonnaya, Ngozi P; Ndubuisi, Ifeoma F; Ekechukwu, Echezona N.D; Okoronkwo, Ijeoma L; Onwujekwe, Obinna
ABSTRACT: Infection with HIV/AIDS continues to be a major public health concern around the world, particularly in low- and middle-income nations. To assess the effectiveness of structured health education on the prevention of HIV/AIDS risky behaviours among adolescents in secondary school. A pretest-posttest-control group randomized controlled trial where a sample of 647 adolescents was drawn from the population of 2, 890 secondary school students and was block-randomized into the intervention (n = 400) and control (n = 224) groups. Data were collected using a content-validated (CVI = 4.2/5) and reliable (k = 0.791) self-developed structured questionnaire. Data were analyzed using descriptive statistics and with inferential statistics of independent and paired t-tests at α = 0.05. Pre-intervention risky behaviours in both groups were below average though lower in the intervention than in the control group. Pre-intervention risky behaviour was significantly higher among males than females in the rural school (p < 0.001) and in both schools together (p < 0.001). Health education significantly affected risky behaviour with the intervention group being associated with lesser risky behaviour than the control group. There was no significant difference in the post-intervention risky behaviour between males and females in the rural (0.285), urban (0.179) and both schools together (p = 0.956). Post-intervention reduced risky behaviours more significantly in the intervention than in the control groups. HIV/AIDS health education should be part of schools' curriculum, guidance and counsellor teachers should be trained as HIV counsellors